Birth of the Communist Manifesto. With full text of the "Manifesto", all prefaces by Marx and Engels, early drafts by Engels and other supplementary material. Ed. and annotated, with an introd. by D.J. Struik (International Publishers, 1971)
With ills, index and prts. New World paperbacks, NW-140.